THE EFFECT OF SILODOSIN AND SODIUM DICLOFENAC TO REDUCE PAIN AFTER DJ STENT REMOVAL IN SOETOMO HOSPITAL: DOUBLE-BLINDED RANDOMIZED-CONTROLLED TRIAL - Fathurrahman, Hasroni; Soebadi, Doddy M; Hakim, Lukman (Indonesian Journal of Urology, 2019)
Objective: To analyze, measure, compare, prove, and evaluate effectiveness of silodosin, diclofenac sodium, and the combination of both drugs in pain management after stent removal. Materials & Methods: Thirty-three patients were divided into three groups. Group I was given diclofenac Sodium 50 mg, group II was given silodosin 8 mg and group III was given the combination of diclofenac sodium 50 mg and silodosin 8 mg. The Wong Baker Pain Scale (WBPS) was assessed serially: two hours before the DJ stent removal, during DJ stent removal, and after the DJ stent removal (2 hours and 24 hours after). The data was analyzed by ANOVA and Kruskal-Wallis test. Results: In this study, 33 patients who underwent DJ stent removal were obtained. Wong Baker was presented in median (min-max) form. The WBPS study in each group did not differ statistically significant. Lowest WBPS during DJ stent removal was found in group III. Group III was better and statistically significant in reducing pain compared to group I and group II (p<0.05). WBPS two hours after removal in each group decreased and group III was better and statistically significant in reducing pain compared to group II, whereas group III compared to group I had an equivalent effectiveness. While the WBPS 24 hours after removal had the same value and did not differ significantly. No side effects or adverse events were found in the use of diclofenac sodium, silodosin, and their combinations. Conclusion: Single oral dose of diclofenac sodium combined with silodosin is effective to reduce pain after DJ stent removal.